Grammars about fire and water in São Paulo’s sugarcane fields - Jéssica Pires Cardoso; Ana Carina Sabadin; Rodrigo Constante Martins (Ambiente & Sociedade)
Abstract This article takes a closer look at the strategies for naming water and fire in the grammar of sugarcane production in São Paulo - themes that gained centrality in socio-environmental regulations aimed at this production in the first decade of the 2000s. The empirical universe of the research is located in the administrative region of Ribeirão Preto, whose borders are home to a strong presence of mills and sugarcane plantations, as well as an abundance of surface and underground water. The hypothesis is that this grammar operates strategically in response to socio-environmental criticism, while these names take on different facets depending on concrete disputes and situations. Methodological resources include a literature review, a survey and documentary analysis, semi-structured interviews with representatives of the sugar mills and sugarcane suppliers’ associations, as well as the monitoring of lives promoted by CETESB and CanaOnline.